BAX INHIBITOR-1 Is Required for Full Susceptibility of Barley to Powdery Mildew - Ruth Eichmann; Melanie Bischof; Corina Weis; Jane Shaw; Christophe Lacomme; Patrick Schweizer; Dimitar Duchkov; Götz Hensel; Jochen Kumlehn; Ralph Hückelhoven (Molecular Plant-Microbe Interactions, 2010)
BAX INHIBITOR-1 (BI-1) is one of the few proteins known to have cross-kingdom conserved functions in negative control of programmed cell death. Additionally, barley BI-1 (HvBI-1) suppresses defense responses and basal resistance to the powdery mildew fungus Blumeria graminis f. sp. hordei and enhances resistance to cell death–provoking fungi when overexpressed in barley. Downregulation of HvBI-1 by transient-induced gene silencing or virus-induced gene silencing limited susceptibility to B. graminis f. sp. hordei, suggesting that HvBI-1 is a susceptibility factor toward powdery mildew. Transient silencing of BI-1 did not limit supersusceptibility induced by overexpression of MLO. Transgenic barley plants harboring an HvBI-1 RNA interference (RNAi) construct displayed lower levels of HvBI-1 transcripts and were less susceptible to powdery mildew than wild-type plants. At the cellular level, HvBI-1 RNAi plants had enhanced resistance to penetration by B. graminis f. sp. hordei. These data support a function of BI-1 in modulating cell-wall-associated defense and in establishing full compatibility of B. graminis f. sp. hordei with barley.